Nuclear factor kappa B inhibition improves conductance artery function in type 2 diabetic mice. Issue 1 (January 2015) - Kassan, Modar; Choi, Soo‐Kyoung; Galán, Maria; Trebak, Mohamed; Belmadani, Souad; Matrougui, Khalid
Abstract Background We previously reported that enhanced nuclear factor kappa B (NFκB) activity is responsible for resistance arteries dysfunction in type 2 diabetic mice. Methods In this study, we aimed to determine whether augmented NFκB activity also impairs conductance artery (thoracic aorta) function in type 2 diabetic mice. We treated type 2 diabetic (db−/db−) and control (db−/db+) mice with two NFκB inhibitors (dehydroxymethylepoxyquinomicin, 6 mg/kg, twice a week and IKK‐NBD peptide, 500 µg/kg/day) for 4 weeks. Results As expected, the NFκB inhibition did not affect blood glucose level and body weight. Thoracic aorta vascular endothelium‐dependent relaxation (EDR), determined by the wire myograph, was impaired in diabetic mice compared with control and was significantly improved after NFκB inhibition. Interestingly, thoracic EDR was also rescued in db−/db−p50NFκB−/− and db−/db−PARP‐1−/− double knockout mice compared with db−/db− mice. Similarly, the acute in vitro down regulation of NFκB‐p65 using p65 shRNA lentiviral particles in arteries from db−/db− mice also improved thoracic aorta EDR. Western blot analysis showed that the p65NFκB phosphorylation, cleaved PARP‐1 and COX‐2 expression were increased in thoracic aorta from diabetic mice, which were restored after NFκB inhibition and in db−/db−p−50NFκB−/− and db−/db−PARP‐1−/− mice. Conclusions The present results indicate that in male type 2 diabetic mice, the augmented NFκB activity also impairs conductance artery function through PARP‐1 and COX‐2‐dependent mechanisms. Copyright © 2014 John Wiley & Sons, Ltd.